2007
DOI: 10.1186/bf03352718
|View full text |Cite|
|
Sign up to set email alerts
|

Magnitude determination using duration of high frequency energy radiation and displacement amplitude: application to tsunami earthquakes

Abstract: Recently, we developed a new method to determine earthquake magnitudes using durations of high frequency energy radiation and the maximum displacement amplitudes, which can be measured from processing of first arriving P-waves. In the present study, we applied this method to the 1992 Nicaragua, 1994 Java, 1996 Peru, and 2006 Java earthquakes which have been suggested to be "tsunami earthquakes." Our magnitude estimates for these earthquakes are consistent with the moment magnitudes in the Global CMT catalog, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Several magnitude determination methods have been proposed for a tsunami warning based on P-wave before the S-wave arrival (Tsuboi et al, 1995;Yoshida, 1995;Hara, 2007;Kanamori and Rivera, 2008;Lomax and Michelini, 2009). When the fault rupture lasts a long time, the epicentral distance of data should be great enough to get a T S − T P exceeding the rupture duration, where T P and T S are the travel times of P and S waves.…”
Section: Introductionmentioning
confidence: 99%
“…Several magnitude determination methods have been proposed for a tsunami warning based on P-wave before the S-wave arrival (Tsuboi et al, 1995;Yoshida, 1995;Hara, 2007;Kanamori and Rivera, 2008;Lomax and Michelini, 2009). When the fault rupture lasts a long time, the epicentral distance of data should be great enough to get a T S − T P exceeding the rupture duration, where T P and T S are the travel times of P and S waves.…”
Section: Introductionmentioning
confidence: 99%
“…Tsunami earthquakes generate unusually large tsunami waves relative to their surface wave magnitudes (Kanamori, 1972) and are characterized by several common factors, such as long source durations, depletion in high-frequency radiation, and the proximity of their source region to the trench axis (e.g., Pelayo and Wiens, 1992;Polet and Kanamori, 2000;Hara, 2007). Thrust-faulting along the shallow part of the plate boundary is the candidate source of the tsunami earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed a method to determine earthquake magnitudes using durations of P-wave high-frequency energy radiation and maximum displacement amplitudes (Hara, 2007a). We have also shown that this method is applicable to tsunami earthquakes (Hara, 2007b).…”
Section: Introductionmentioning
confidence: 99%